Finally about Infinity. Leibniz’s Dialogue Pacidius Philalethi is Translated into Czech - Kadlečíková, Jitka (Teorie vědy / Theory of Science, 2023)
Book review: Leibniz, Gottfried Wilhelm. Pacidius Philalethi – Pacidius Philalethovi. Přeložil Jan Makovský. Praha: Oikoymenh, 2019. 341 stran.